Characterization of a settled dust event in an urban area affected by industrial activities - Gamelas ou Carla A. Gamelas, Carla (2021)
Trabalho apresentado em 7th Iberian Meeting Aerosol Science and Technology – RICTA19, 2019, Lisbon, Portugal